Optical Wireless Communications with Metasurfaces: Current Status and Potential for Intelligent Communications - Ke Wang; Chengwei Fang; Md Osman Ali; Xiaojun Chen; Safa Alghadi; Shuo Li; Jiayuan He; Sithamparanathan Kandeepan (Advanced Photonics Research)
Optical wireless communications (OWCs) provide a promising alternative to current spectrum‐congested microwave wireless communications by directly transmitting data‐modulated lightwave in the free space. Due to the broad unregulated bandwidth, high‐speed data transmissions are achieved. However, direct line‐of‐sight links are required in OWC systems, and typically only point‐to‐point or limited point‐to‐multi‐point connections can be achieved, limiting the communication robustness and user movements. In addition, accurate alignment between transceivers is required to maintain the high‐speed optical link, demanding adaptive beam control functions. To solve these constraints, the use of intelligent metasurfaces for dynamic beam steering and beam manipulation in OWCs is proposed and investigated. Such metasurfaces with sub‐wavelength features also enable other versatile functions like spatial‐ or optical‐angular‐momentum‐mode generation, conversion, and multiplexing, further improving the communication performance and capability of OWCs. In this article, the recent progress is summarized and the view on the possible future research directions in this emerging field that incorporates OWCs with metasurfaces is provided.